The Pathways to Desistance: A Longitudinal Study of Juvenile Delinquency. Issue 1 (2nd January 2020) - Lee, Wanhee; Moon, Junseob; Garcia, Venessa
ABSTRACT: Although longitudinal studies of developmental trajectories of juvenile offending have been ongoing for over two decades, longitudinal studies on desistance trajectories are lacking. The purpose of this study is to identify adolescents who desist from delinquent behaviors while still in their adolescence. The study also examines the roles of parental attachment and low self-control in the prediction of identified desistance pathways using data from the Korean Youth Panel Study (KYPS), a five-year longitudinal study of South Korean youth. In an analysis of latent growth model, this study suggests that low self-control is strongly related to juvenile desistance trajectories. In addition, there is evidence of an indirect relationship between parental attachment and desistance. The results from this analysis will be examined in light of previous findings. Theoretical and policy implications are discussed.